Neuronal Activity in the Hibernating Brain - Sonntag, Mandy; Arendt, Thomas (Frontiers in Neuroanatomy, 2019)
Hibernation is a natural phenomenon in many species which helps them to survive under extreme ambient conditions, such as cold temperatures and reduced availability of food in the winter months. It is characterized by a dramatic and regulated drop of body temperature, which in some cases can be near 0°C. Additionally, neural control of hibernation is maintained over all phases of a hibernation bout, including entrance into, during and arousal from torpor, despite a marked decrease in overall neural activity in torpor. In the present review we provide an overview on what we know about neuronal activity in the hibernating brain focusing on cold-induced adaptations. We discuss pioneer and more recent in vitro and in vivo electrophysiological data and molecular analyses of activity markers which strikingly contributed to our understanding of the brain’s sensitivity to dramatic changes in temperature across the hibernation cycle. Neuronal activity is markedly reduced with decreasing body temperature, and many neurons may fire infrequently in torpor at low brain temperatures. Still, there is convincing evidence that specific regions maintain their ability to generate action potentials in deep torpor, at least in response to adequate stimuli. Those regions include the peripheral system and primary central regions. However, further experiments on neuronal activity are needed to more precisely determine temperature effects on neuronal activity in specific cell types and specific brain nuclei.